Evaluation of the Eating Attitude of Handball Players - Samar, Ezgi; Togay Unaldi, Gamze (Progress in Nutrition, 2021)
Study Objectives: This study aimed to evaluate the eating attitudes of handball players according to some variables. Methods: One hundred twenty volunteer handball players participated in the study. The questionnaire consisted of the information questionnaire that determined the demographic characteristics and the eating attitude test EAT-26, which was adapted to Turkish by Devran (2014). After the scales were prepared on google-form, the research was announced on social media, and participation was provided voluntarily. When the data used in the study were analyzed with the Kolmogorov-Smirnov test, the Mann-Whitney U, and Kruskal-Wallis tests, which were nonparametric. Results: In the study, normal eating attitudes and behaviors were observed in 83.3% of the athletes, and abnormal eating attitudes and behaviors were observed in 16.7%. When the eating attitude scores of the athletes were compared according to the variables of gender, nutrition program implementation, dietitian support, and body weight perception, a statistically significant difference was observed, and no difference was observed in terms of age, educational status, sports age, weekly training time (p